(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Environmental concerns and the rising cost of fossil fuels have prompted a significant increase in the use of renewable energy sources. The amount of electricity produced has an impact on the integration of renewable energy with utility infrastructure. Large-scale power generation is connected to transmission networks, while small-scale distributed power generation is connected to distribution networks. The direct integration of both kinds of technologies creates certain challenges. As a result, wind energy has attracted significant investment from throughout the globe. However, it is difficult to acquire excellent quality electricity owing to the unpredictability of wind speed, because wind speed changes affect the voltage or active energy density of the electric machine attached to the wind turbine. Solar perforation alters the voltage stability or frequency responsiveness of the system, as well as the utility grid’s generation or distribution systems. The potential of power storage technology to improve the integration of renewable into the smart grid is examined in this paper, as well as the concerns, challenges, and usage of renewable sources (RES) Grid Integration. In this paper, author talks about renewable energy integration in smart grid. Renewables are expected to account for about 95percent of the growth in worldwide power capacity by 2026, and solar PV accounting for more than half of it. Between 2021 and 2026, the quantity of renewable capacity installed is predicted to be 50% more than between 2015 and 2020.